Perancangan dan Analisis Sistem Informasi Pelayanan Kependudukan - Nasir Suruali (Industrial Engineering Study Program, Pattimura University, 2015)
Civil registration services, as a product of Population and Civil Registration Agency, has operated with bureaucracy that take a lot of time to complete. Since internet network become information sharing tool to support local development, putting service application of civil registration in network will change performance of the present system and have a high level of efficiency and affectivity. The designed application in this research are administration system of civil registration, especially to produce a Birth Certificate using biometric (finger print) as an identification and management system documents using database server. This application must be interactive because has been developed to enhance the performance of personnel department staffs and simultaneously performing common perception among staffs of the agency, villages/kelurahan and hospital (the places to enter the application data of civil registration) and related institutions such as local government, KPU and BPS. Application systems designed are using object-oriented analysis and design (OOAD) method with UML as modeling language.